2020
DOI: 10.1186/s12888-020-2466-z
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and acceptability of a novel community-based mental health intervention delivered by community volunteers in Maharashtra, India: the Atmiyata programme

Abstract: Background: Many community-based intervention models for mental health and wellbeing have undergone robust experimental evaluation; however, there are limited accounts of the implementation of these evidencebased interventions in practice. Atmiyata piloted the implementation of a community-led intervention to identify and understand the challenges of delivering such an intervention. The goal of the pilot evaluation is to identify factors important for larger-scale implementation across an entire district in In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…They found the intervention worthy of their time and looked forward to the sessions. Their responses were similar to another lay-led community-based mental health intervention with qualitative findings that reported reduced depressive moods and improved social functioning in adults [50]. They also suggested changing the recruitment process to appeal to more potential participants and have more informative and mindfulness training sessions for better insight.…”
Section: Discussionmentioning
confidence: 66%
“…They found the intervention worthy of their time and looked forward to the sessions. Their responses were similar to another lay-led community-based mental health intervention with qualitative findings that reported reduced depressive moods and improved social functioning in adults [50]. They also suggested changing the recruitment process to appeal to more potential participants and have more informative and mindfulness training sessions for better insight.…”
Section: Discussionmentioning
confidence: 66%
“…Mitras receive one day of training, during which they are paired with Champions for support ( 50 ). A randomized, controlled trial of the Atmiyata program found that Champions were able to accurately identify people with emotional distress, and, after six counseling sessions, the proportion of participants with elevated symptoms dropped from 63.8 to 36.8% ( 52 ). While this program is based entirely within community settings, there is a mechanism through which lay health workers can refer individuals with more serious mental disorders to higher-level care ( 52 ).…”
Section: Resultsmentioning
confidence: 99%
“…A randomized, controlled trial of the Atmiyata program found that Champions were able to accurately identify people with emotional distress, and, after six counseling sessions, the proportion of participants with elevated symptoms dropped from 63.8 to 36.8% ( 52 ). While this program is based entirely within community settings, there is a mechanism through which lay health workers can refer individuals with more serious mental disorders to higher-level care ( 52 ). To ensure ongoing support and supervision of the Atmiyata Champions and Mitras, remote approaches utilizing mobile phones were combined with in-person supervision sessions ( 52 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Community Mental Health Services (CMHS) is a common development in mental health services worldwide [14]. It positively affects reducing to utilize other services, reducing stigma, improving help-seeking attitudes, and promoting mental health [15][16][17]. Many Central and Eastern European countries have been working to develop CMHS [18].…”
Section: Introductionmentioning
confidence: 99%